Legal analysis of the banten province regional personnel agency policy in recruiting employees at the cilograng regional general hospital and the Labuan - Alif Surachman; Asnawi Asnawi; Faturohman Faturohman (Institute Of computer Science (IOCS), 2024)
This research analyzes the legal aspects of the Banten Province Regional Personnel Agency (BKD) policy in recruiting employees at Cilograng Regional General Hospital and Labuan Regional General Hospital in relation to Banten Governor Regulation Number 11 of 2020 concerning the governance of non-civil servant employees at the Regional Public Service Agency (BLUD) within the Banten Provincial Health Service. Using a normative juridical approach supported by empirical data, this study examines the extent to which recruitment practices comply with the regulatory framework and principles of good governance. The findings show that while the recruitment process largely follows the Governor Regulation, challenges remain in ensuring transparency, accountability, and equal opportunity. The BLUD system provides flexibility for hospitals to address human resource needs more quickly; however, weaknesses in oversight mechanisms and the lack of legal certainty for non-civil servant employees may create legal and administrative risks. The study recommends clearer technical guidelines and consistent monitoring to strengthen compliance and improve governance in recruitment. It is necessary to increase the capacity of the selection committee through training on the principles of good governance and the use of information technology in the recruitment process, so that transparency, accountability, and equal opportunities can be more assured.